2007
DOI: 10.1002/hep.21766
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic and duodenal homeobox gene 1 induces hepatic dedifferentiation by suppressing the expression of CCAAT/enhancer-binding protein β

Abstract: It is believed that adult tissues in mammals lack the plasticity needed to assume new developmental fates because of the absence of efficient pathways of dedifferentiation. However, the well-documented ability of the transcription factor pancreatic and duodenal homeobox gene 1 (PDX-1) to activate pancreatic lineage development and insulin production following ectopic expression in liver suggests a surprising degree of residual plasticity in adult liver cells. This study seeks a mechanistic explanation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…Dedifferentiation is often associated with carcinogenesis and has been named 'anaplasia', that is, reversion of cells to an immature or a less-differentiated form. Besides tumors (Helm et al, 2005), these cells are found in muscle tissue (Chen et al, 2005), nervous tissue (Harrisingh et al, 2004;Sunico & Moreno-Lopez, 2010), renal tissue (Lluis et al, 2008), myocardial tissue (Jopling et al, 2010), hepatic tissue (Meivar-Levy et al, 2007), chondrocytes (Gustafson & Smith, 2010;Kiesslich et al, 2010), and others. In epidermal tissue, dedifferentiation-derived epidermal stem cell-like cells were found in spinous and granular layers of (Fu et al, 2001;Li et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation is often associated with carcinogenesis and has been named 'anaplasia', that is, reversion of cells to an immature or a less-differentiated form. Besides tumors (Helm et al, 2005), these cells are found in muscle tissue (Chen et al, 2005), nervous tissue (Harrisingh et al, 2004;Sunico & Moreno-Lopez, 2010), renal tissue (Lluis et al, 2008), myocardial tissue (Jopling et al, 2010), hepatic tissue (Meivar-Levy et al, 2007), chondrocytes (Gustafson & Smith, 2010;Kiesslich et al, 2010), and others. In epidermal tissue, dedifferentiation-derived epidermal stem cell-like cells were found in spinous and granular layers of (Fu et al, 2001;Li et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of human liver cells was performed as described (3,5). The cells were cultured in Dulbecco's minimal essential medium (1 g/liter of glucose) supplemented with 10% fetal calf serum, exendin-4 (5 nM; Sigma), epidermal growth factor (20 ng/ml; Cytolab, Ltd.), and nicotinamide (10 mM; Sigma) and kept at 37°C in a humidified atmosphere of 5% CO 2 and 95% air.…”
Section: Methodsmentioning
confidence: 99%
“…The adenoviruses used in this study were as follows: Ad-CMV-PDX-1, Ad-RIP-GFP (3,5), Ad-CMV-GFP (Clontech), and Ad-GLUP-RED. Ad-GLUP-RED was prepared by insertion of 350 nucleotides of the 5Ј-flanking region of the rat glucagon promoter (generous gift from A. Manin) in the pACCMV.pLpA plasmid to drive ds-red2-n1 gene expression (KpnI/NotI, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations